The Association Between METS-IR and Serum Ferritin Level in United States Female: A Cross-Sectional Study Based on NHANES - Hao, Han; Chen, Yan; Xiaojuan, Ji; Siqi, Zhang; Hailiang, Chu; Xiaoxing, Sun; Qikai, Wang; Mingquan, Xing; Jiangzhou, Feng; Hongfeng, Ge (Frontiers in Medicine, 2022)
Abstract Aim: The aim of this study was to investigate the association between the metabolic score for insulin resistance (METS-IR) and serum ferritin in females from the United States. Methods: We conducted a cross-sectional study with 4182 participants from the National Health and Nutrition Examination Survey (NHANES). We used METS-IR and serum ferritin as the independent and dependent variables in this study and investigated the relationship by using multiple linear regression and verified the non-linear relationship with a smooth curve fit and threshold effect model. Results: There was a positive relationship between METS-IR and serum ferritin, with an effect value of (β = 0.29, 95% CI: 0.14 to 0.44) in a fully adjusted model adjusted for potential confounders. This positive correlation became more significant as METS-IR increased (p for trend < 0.001). Subsequent subgroup analyses showed that sensitive cohorts were those aged ≥40 years, black, and with a body mass index (BMI) <24.9 kg/m2. In a smoothed curve fit analysis, the correlation between METS-IR and serum ferritin was a straight linear relationship in all participants included in this study, but when stratified by age, race, and BMI, this positive correlation in the participants who were aged ≥40 years old, other race, and had a BMI <24.9 kg/m2 was non-linear. Conclusions: There was a positive association between METS-IR and serum ferritin in United States females, and this positive association was more pronounced in participants aged ≥40 years, black race and BMI <24.9 kg/m2. This positive association was non-linear in the subgroups aged ≥40 years, white race and BMI <24.9 kg/m2, with inflection points for METS-IR of 69.97, 67.84 and 35.84 in these respective subgroups.